Teacher Digital Skill After Covid 19 In Public Senior High School - Muslim, Fachruddiansyah; Nasori, Ahmad; Firman; Mayasari (Eduscape : Journal of Education Insight, 2024)
The purpose  of this study was to determine the description of digital skills owned by teachers and compare them based on school type. This research uses mixed method with The Explanatory Sequential Design type. This research uses purposive sampling technique. The sample of this research is a teacher at one of the schools selected based on the type of school, namely SMA, SMK and MAN. Kruskal-Wallish test and Mann Whittney test were used to determine the differences in digital skills owned by teachers. The results showed that the digital skills possessed by teachers based on the type of school, it is known that there are differences in digital skills possessed. The digital skills possessed by teachers are included in the high and very high categories and when compared in each school it is known that there is no difference between the digital skills of SMK and SMA, SMK and MAN teachers. Then in the qualitative analysis in the digital skill indicator section, the teacher has done very well in an effort to carry out his job as a teacher, but the aspects of Digital Content Creation and safety need to be improved. The real implication of this research is the ability for teachers to apply digital skills such as knowledge and attitudes in a confident, critical and responsible manner within the specified context as required